Development of Nusantara Card Media in Learning IPS Class IV Elementary School - Jeliwanti, Mesy Kholina; Idris, Muhamad; Aryaningrum, Kiki (Journal of Social Work and Science Education, 2023)
Social studies learning requires learning media that can improve the learning achievement of grade IV students. This research is a type of R&D (Research and Development) research using the 3D model (Define, Design, Development). The purpose of this research is to produce a product of Nusantara cards on social studies learning grade IV. The problems found by teachers tend to use the lecture method, rarely use learning media, especially in social studies material, so that students’ understanding of social studies learning material is still low. This research was conducted at SDN 19 Rambang Niru in class IV. Data collection through questionnaires and documentation. Data analysis in this study obtained validity and practicality. This research and development resulted in a valid archipelago card being used, with a score of 86% in the “very valid” category. Based on the results of the one-two-one trial, the results obtained 84% with the category “very practical”, and in the small group trial obtained 85% with the category “very practical”. It can be concluded that the archipelago card media is suitable for use in social studies learning.